2021
DOI: 10.1155/2021/4334632
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study and Effect on Recycled Fibers Blended with Rotor/OE Yarns for the Production of Handloom Fabrics and Their Properties

Abstract: The uses of recycled materials have gained massive importance in the textile sector and other application areas as the effects of reducing natural resources are felt worldwide. This study aimed to analyze the effects of recycled fiber usage on the properties of OE-rotor spun yarns and hand-woven fabrics produced from these yarns. For this purpose, OE-rotor yarns are produced at different proportion levels from virgin cotton and recycled fibers derived from knitted garment wastes at 25%, 50%, and 75%, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…As shown in Figure 16 (a)–(c), the produced fabrics have a mélange-like appearance and their hand feel is also soft and comfortable. The abrasion- and pilling resistance along with air permeability of the fabrics produced from virgin cotton/recycled fiber blend yarns in rotor spinning were found to be decreased with the proportion of recycled fibers in yarns due to the presence of a high amount of short fibers in yarns ( Awgichew et al., 2021 ). However, the current work focuses on the production of soft (low twist) yarns from pre- and post-consumer recycled fibers in ring spinning suitable for top knit garments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 16 (a)–(c), the produced fabrics have a mélange-like appearance and their hand feel is also soft and comfortable. The abrasion- and pilling resistance along with air permeability of the fabrics produced from virgin cotton/recycled fiber blend yarns in rotor spinning were found to be decreased with the proportion of recycled fibers in yarns due to the presence of a high amount of short fibers in yarns ( Awgichew et al., 2021 ). However, the current work focuses on the production of soft (low twist) yarns from pre- and post-consumer recycled fibers in ring spinning suitable for top knit garments.…”
Section: Resultsmentioning
confidence: 99%
“…To get rid of this problem, virgin fibers are blended with recycled fibers those act as carriers during the spinning process, and using this technique, coarser yarns were produced in rotor spinning system ( Ute et al., 2019 ; Yuksekkaya et al., 2016 ). For instance, 10–20 Ne rotor yarns were produced from virgin cotton and recycled fibers derived from garment wastes with different blend ratios (cotton: recycled fibers 10:90 to 75:25) ( Memon et al., 2022 ; Kanan et al., 2022 ; Awgichew et al., 2021 ; Jamshaid et al., 2021 ; Ute et al., 2019 ). Rotor spinning is limited to producing only coarser yarns (theoretically up to 24 Ne, commercially up to 20 Ne).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have already studied the effect of waste on yarn quality from different perspectives. The results of several investigations have revealed that the waste of different sections of the apparel industry significantly affects the physical and mechanical properties of the yarn [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Jamshaid et al.…”
Section: Introductionmentioning
confidence: 99%
“…Awgichew et al. [ 12 ] investigated the impact of the use of recycled fibers on OE-rotor yarns manufactured of 100% virgin cotton and virgin cotton/recycled fiber blends in various proportions (25%, 50% and 75%). The tensile strength of recycled blended yarns is higher than that of virgin yarns.…”
Section: Introductionmentioning
confidence: 99%
“…Extreme production in the textile business is fueled in part by the fashion industry's belief that consumers require a new wardrobe for each season. This raises the rate of product exchange as well as the rate of fabric and waste generation [1]. This increases the exchange rate of products and the rate of fabric and waste production.…”
Section: Introductionmentioning
confidence: 99%